'Speaking volumes': A longitudinal study of lexical and grammatical growth between 17 and 42 months. Issue 2 (April 2014) - Labrell, Florence; van Geert, Paul; Declercq, Christelle; Baltazart, Véronique; Caillies, Stéphanie; Olivier, Marie; Le Sourn-Bissaoui, Sandrine
Dynamic analyses of language growth tell us how vocabulary and grammar develop and how the two might be intertwined. Analyses of growth curves between 17 and 42 months, based on longitudinal data for 34 children, revealed interesting patterns of vocabulary and grammatical developments. They showed that these patterns were nonlinear, but with coinciding peaks of growth, suggesting a bilateral relationship between acquisition of vocabulary and grammar. A more detailed analysis of specific components of vocabulary (nouns, verbs, grammatical words) and grammar showed that each followed its own developmental course, but that its growth rates were likely to be negatively or positively correlated with those of other components. For example, a faster rate for acquiring nouns coincided with a slower rate for verbs. Last, an assessment of intra-individual variability in three children showed that mean scores obscure individual profiles.